2020
DOI: 10.1097/pq9.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Approach to Reduce Unplanned Extubation in the NICU While Avoiding Sedation and Restraints

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Given the potential short- and long-term consequences of UEs and the associated increased healthcare costs, UE prevention has become an important focus of quality improvement (QI) efforts for NICU patients. Because single-center QI initiatives have been successful in reducing UEs in the NICU [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and one NICU among our regional perinatal centers (RPC) had been working to improve UE locally without much success, we proposed a multi-center QI collaborative as a model to drive improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential short- and long-term consequences of UEs and the associated increased healthcare costs, UE prevention has become an important focus of quality improvement (QI) efforts for NICU patients. Because single-center QI initiatives have been successful in reducing UEs in the NICU [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and one NICU among our regional perinatal centers (RPC) had been working to improve UE locally without much success, we proposed a multi-center QI collaborative as a model to drive improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The containment of patients with band restraint was already prohibited in our institution and strongly criticised in the literature about its use. 26 28 29 The project team was in search of a model that would provide a less restrictive alternative, and the challenge was to find a national company that would manufacture a model similar to those used internationally, which was a great differential in the way of providing adequate restriction and comfortable in the paediatric population, that is, effective according to best practices. These new models provide limitations in movements with restriction of elbow flexion and pinch of the fingers with comfort and prevention of accidental exit of the traction devices.…”
Section: Discussionmentioning
confidence: 99%
“…25 Adequacy of sedation is a subject that presents many challenges because sedation for the prevention of agitation and consequently the prevention of UE can lead to excessive levels of sedation, increasing the duration of mechanical ventilation and length of hospital stay. 26 According to Society of Critical Care Medicine Clinical Practice Guidelines Finding a balance between oversedation and undersedation is paramount. That guideline suggests the use of COMFORT-B scale to evaluate the ideal depth of sedation, the same scale used for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly focused on strategies to reduce the incidence of unplanned extubation (UE) of the endotracheal tube (ETT). Unplanned extubation (UE) or accidental displacement of the ETT can cause common adverse effects in patients, including lung collapse, cardiovascular instability, trauma to the upper respiratory tract, ventilator-associated pneumonia, and so on [17]. A study including 182 neonates requiring mechanical ventilation in Australia showed that the UE rate in the neonatal population was 4.75 per 100 days of ventilation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the team implemented various interventions in the NICU to prevent unplanned removal, such as changing the ETT taping method, increasing the contact surface area of the adhesion, and avoiding loose securement. After implementation of quality improvement approaches, the incidence of UEs decreased dramatically while avoiding the need for sedation and restraints [23].…”
Section: Discussionmentioning
confidence: 99%